Association between the preoperative geriatric nutritional risk index and loss of walking independence 180 days after hip fracture surgery: A retrospective cohort study - Jiachen Ren; Mengyuan Liu; Keyao Yang; Cici Bai; Xu Ma; Zhishang Wang; Guoxin Dong; Yanbin Zhu; Xiuting Li (Aging Clinical and Experimental Research, 2026)
Abstract Background Malnutrition may impair recovery after hip fracture, but the association between preoperative geriatric nutritional risk index (GNRI) and postoperative walking outcomes remains unclear. We examined the association between GNRI and loss of walking independence (LWI) 180 days after hip fracture surgery. Methods This was a retrospective cohort study of patients aged 65 years and older who sustained a hip fracture and underwent surgery at a tertiary referral hospital between January 2021 and December 2023. The exposure was the GNRI, calculated based on admission blood test results using the following formula: 1.489 × serum albumin concentration [g/L] + 41.7 × (actual bodyweight / ideal bodyweight). LWI was defined as a Functional Independence Measure–Locomotion score ≤ 5 at telephone follow-up. Restricted cubic spline (RCS) was used to assess the shape of the association. Multivariable logistic regression estimated the odds ratio (OR) for LWI per 10-point decrease in GNRI. Robustness was evaluated using multiple sensitivity and prespecified subgroup analyses. Results The cohort consisted of 1,345 patients (925 female [68.8%]; median [Q1-Q3] age, 76 [69–82] years), with 622 patients with LWI (46.2%) by 180 days. RCS analysis showed that lower GNRI values were linearly associated with higher odds of LWI (P for overall association = 0.003; P for nonlinearity = 0.326). After adjustment, each 10-point decrease in GNRI was associated with higher odds of LWI (adjusted OR, 1.30; 95% confidence interval, 1.13–1.52; P < 0.001). Results were generally consistent across sensitivity and subgroup analyses, with no significant heterogeneity after correction for multiple testing. Conclusion Lower preoperative GNRI was associated with higher odds of LWI 180 days after hip fracture surgery. GNRI may be considered as one component of a comprehensive preoperative assessment, but should not be used as a stand-alone prognostic tool. The trial registration number (TRN): ChiCTR-PPC-14005360.